Design And Construction Of A Kinetic Power Generator Using A Paving Generator On The Sideway As A Supply For Street Lamps In The Medan Aviation Polytechnic Campus - Tampubolon, Iwan Henri; Usman, Usman; Magdalena, Sartika; Chair, Achmad (STABN RADEN WIJAYA WONOGIRI, 2024)
This study aims to design and develop a kinetic power generation device that utilizes the mechanical energy from pedestrian foot pressure on sidewalks. The working principle of the system is to convert mechanical energy into electrical energy using eight 12V DC car central lock actuators arranged in a series-parallel configuration. The electrical energy generated from foot pressure is directed into an electronic circuit consisting of diodes as reverse current protection, a DC-DC step-down converter to reduce voltage, and a charge controller to regulate the charging process of a 6800 mAh lithium-ion battery. The stored energy is then boosted using a DC-DC step-up converter to match the load requirements, which is a 10W LED lamp operating at 5V DC. To support monitoring, the circuit is equipped with a control panel containing a digital voltmeter and ammeter with an LCD display that shows voltage and current conditions in real time. All components are regularly assembled inside a panel box mounted on a mini light pole, ensuring practicality and safety in operation. The test results show that the device is capable of producing an average maximum voltage of 14.83 V with a current of up to 25 mA when all central lock actuators are pressed simultaneously. The stored energy in the battery can be used to power the LED lamp for several hours, depending on the intensity and frequency of pedestrian footsteps. With its simple design, easily obtainable components, and relatively low production cost, this system has the potential to serve as an alternative solution in supporting energy efficiency and the application of renewable energy-based lighting systems in campus environments as well as other public areas